Separation of Heart Sounds & Lung Sounds using Independent Component Analysis - B.HemaKumar; R.Anandanatarajan (Universiti Malaysia Perlis, 2010)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.